The Alhambra at the crossroads of history - Eldem, Edhem, 1960- (Edinburgh)
viii, 384 sayfa
Keywords: “A growing flow of visitors in the 19th century turned the Alhambra into a touristic destination and a major trope of Orientalism, created by Western authors and artists from François-René de Chateaubriand to Owen Jones and from Washington Irving to Jean-Léon Gérôme. Yet behind this Western infatuation lie scores of ‘Oriental’ observers of the monument, as revealed by its visitors’ book, kept since 1829. This book uses this untapped source to analyse the perceptions of the Alhambra by multiple actors, including Westerners, Spaniards, Maghrebines, Ottoman Turks, Christian Arabs and Muslim Arabs from the Mashreq. In doing so, it reveals the existence of significant variations in both Western and Oriental perceptions of the monument, from ‘Oriental Orientalism’ to Arab nationalism. Examining the contemporary press, memoirs, travelogues and photographs – as well as the visitors’ book – it uses the Alhambra to build a history of the complex and entangled relations between East and West, North and South, Islam and Christianity, centre and periphery during the heyday of Orientalism and Western hegemony” --